Pengaruh Job Insecurity terhadap Turnover Intention pada Karyawan PT Timah (Persero) Tbk Pangkal Pinang - Bangka Belitung - Lestari, Betaria; Andriana, Isni; Farla, Wita; Siregar, Lina Dameria (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to find out the effect of job insecurity on turnover intention among employess of PT Timah Tbk Pangkal Pinang. The population of this study are employess of PT Timah Tbk Pangkal Pinang a sampel of 75 respondens is this study using purposive sampling method, meaning that the sample has special criteria according to researchers. The special criteria here are employees who are members division include the HR, Accounting, CSR. In this study the data collection used was primary data obtained from questionnaires which were analyzes using simple linear regression analysis techniqudes so it can be concluded that job insecurity thas significant impact on PT Timah Tbk Pangkal Pinang. Keyword : Job Insecurity, Turnover Intention